2020
DOI: 10.1017/s0962492920000069
|View full text |Cite
|
Sign up to set email alerts
|

The numerics of phase retrieval

Abstract: Phase retrieval, i.e. the problem of recovering a function from the squared magnitude of its Fourier transform, arises in many applications, such as X-ray crystallography, diffraction imaging, optics, quantum mechanics and astronomy. This problem has confounded engineers, physicists, and mathematicians for many decades. Recently, phase retrieval has seen a resurgence in research activity, ignited by new imaging modalities and novel mathematical concepts. As our scientific experiments produce larger and larger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 201 publications
(281 reference statements)
0
32
0
Order By: Relevance
“…Problem (1) may be tackled with conventional optimization algorithms such as gradient descent [14], [15], alternating projections [16], [17], majorization-minimization [18], alternating direction method of multipliers (ADMM) [19], [20], and leveraging the structure of time-frequency measurements [21], [22]. An extensive review of those algorithms from a numerical perspective can be found in [23]. Convex optimization approaches are also considered in [24]- [27] by lifting the problem to a higher dimensional space (i.e., solving a constrained quadratic problem involving xx H ) and relaxing the rank-one constraint.…”
Section: Introductionmentioning
confidence: 99%
“…Problem (1) may be tackled with conventional optimization algorithms such as gradient descent [14], [15], alternating projections [16], [17], majorization-minimization [18], alternating direction method of multipliers (ADMM) [19], [20], and leveraging the structure of time-frequency measurements [21], [22]. An extensive review of those algorithms from a numerical perspective can be found in [23]. Convex optimization approaches are also considered in [24]- [27] by lifting the problem to a higher dimensional space (i.e., solving a constrained quadratic problem involving xx H ) and relaxing the rank-one constraint.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, more general phase retrieval problems, where the intensity of arbitrary linear measurements are given, have been studied. Under certain assumptions on the linear measurements, the phase retrieval problem becomes unique [11,12,23,24]. Using a tensorial lifting, the problem may be exemplarily solved using semi-definite programming [11,12], tensor-free primal-dual methods [5], or polarization techniques [2,56].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction phase retrieval has developed into a legitimate branch of applied mathematics, with links to diverse subjects such as harmonic analysis, algebraic geometry, optimization, numerical analysis, etc. We refer to the review papers [10,8] and their extensive lists of references.…”
Section: Introductionmentioning
confidence: 99%